Impact of usability on continuance usage intention in language learning apps with gamification features - Ulfiah, Ulfiah; Rahthin Rasyadan, Muhammad Faris; Utami, Wening Tyas; Sunardi, Sunardi; Fitria Murad, Dina (Institute of Advanced Engineering and Science, 2025)
With the increasing popularity of language learning applications, gamification has become one of the approaches frequently integrated to enhance continuance usage intention (CUI). However, how the usability of these gamification features influences the intention to continue usage is not yet fully understood. Through the usability testing and system usability scale (SUS) method, this study evaluates the level of usability of gamification features in language learning applications with a novel research approach that also involves specific analysis regarding usability aspects according to Nielsen, including learnability, efficiency, memorability, errors, and satisfaction towards the CUI, categorized through the SUS statements grouping and then processed using the SPSS application. The study results indicate that the SUS scores show above-average scores for all three applications: Duolingo application at 77.08, Elsa Speak at 70, and Cake Learn at 70.58. Other findings suggest that usability aspects generally significantly influence CUI; however, only the satisfaction variable impacts CUI, which was observed only in Duolingo and Elsa Speak. These findings indicate that the overall usability of gamification features positively impacts CUI using language learning applications, thereby implying the need for continuous development.